Analysis of the Advantages and Disadvantages of Simultaneous Elections: Impacts on Indonesian Society and Technical Considerations in Their Implementation - Neng Nur Annisa (Khazanah Sosial, 2020)
This study aims to analyze the advantages and disadvantages of simultaneous elections and identify their impact on society. The formulation of this problem is based on the background of the first simultaneous elections in Indonesia in 2019. The research method used is a qualitative technique with the research subject focusing on the decision of the Constitutional Court Number 14/PUU-XI/2013 and data related to the research object. Data collection was carried out through literature studies and structured interviews with KPPS members and members of the public who have voting rights. Simultaneous elections are part of a government breakthrough that has advantages and disadvantages. Researchers consider this to be very relevant and efficient, with the note that vote counting is not complicated and the human resources involved in organizing simultaneous elections must be managed properly. In this research, a thorough analysis will be carried out to understand the impact of simultaneous elections on Indonesian society and to consider important technical aspects in its implementation.